COGS Accuracy Strategy in the Food & Beverage Business Model (Study at Hakui Café, Tulungagung) - Isyrohil Muyassaroh; Dhiya’u Shidiqy; Della Puspita; Nabila Riski Laili Pertiwi; Mahamadaree Waeno; Rahman Arifin (AL-FALAH : Journal of Islamic Economics, 2026)
Purpose: The Paper aims to determine the strategy for implementing production cost management and setting selling prices at Cafe Hakui 0 Km Tulungagung. Design/Method/Approach: This study uses a descriptive analysis. It implemented a quantitative non-statistical approach with emphasis on numbers, from data collection and analysis to data presentation. This research was conducted at Cafe Hakui Kopi, located at 0 Km Tulungagung, Tamanan Village, Tulungagung District, Tulungagung Regency. Findings: The results of this study confirm that the production costs and selling prices at Hakui Kopi Km 0 Tulungagung for the "best-selling" sample use the traditional method, which only accounts for raw materials. In contrast, the selling price is 100% or twice the production cost. There are differences in how production costs and selling prices are calculated using the company method, the full cost method, and the variable cost method. The difference between the cost of goods sold and the selling price results in a difference in net profit. Using the company method, which includes all cost components, Hakui Kopi Km 0 Tulungagung incurred a loss of -30,295,566 IDR per year, or -2,524,631 IDR per month, or -84,154 IDR per day.Originality/Values: The primary contribution of this study is to address the gap in several methods for calculating the cost of goods sold (COGS) based on existing theory.